Fertility Preservation and Restoration for Patients with Complex Medical Conditions - Goetsch, Allison L.; Kimelman, Dana; Woodruff, Teresa K. (Springer International Publishing : Imprint: Springer, 2017)
This unique book is a comprehensive guide for healthcare providers who treat patients with complex medical conditions but lack the resources to address fertility and sexuality concerns and help patients navigate their fertility decision-making process. It presents up-to-date information concerning fertility preservation and restoration for patients with hereditary cancer syndromes, disorders of sex development, hematologic diseases, genetic disorders of gonadal dysfunction, immunologic diseases, gynecologic diseases, endocrine disorders, and autoimmune and inflammatory diseases. Utilizing a practical, user-friendly format, each chapter discusses the epidemiology, classification, risk factors and/or clinical manifestations, and diagnosis and treatment modalities specific to each condition, as well as the effect of it or its treatment on fertility and unique options that may exist. Complex medical conditions are inherently difficult to manage, and reproductive interventions are often not part of the conversation. As such, Fertility Preservation and Restoration for Patients with Complex Medical Conditions will be an excellent resource for primary care physicians, obstetrician/gynecologists, endocrinologists, oncologists, and other health professionals working with patients with fertility concerns.
Keywords: Medicine.; Endocrinology.; Reproductive medicine.; elektronické knihy; electronic books